2021
DOI: 10.1038/s41598-021-84704-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for distant metastasis in locoregionally controlled oral squamous cell carcinoma: a retrospective study

Abstract: The control of distant metastasis in oral squamous cell carcinoma is an important determinant of improved prognosis. The study aimed to identify risk factors for distant metastasis in patients with locoregionally controlled oral carcinoma. We identified 982 patients with oral squamous cell carcinoma treated at our hospital between January 2008 and December 2017. After excluding patients with distant metastasis at initial treatment, patients with metastasis to the oral cavity, those receiving palliative treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
(28 reference statements)
2
12
0
Order By: Relevance
“…In comparison, our study did not reveal any correlations between the localization of the tumor and the occurrence of M+, but it also identified the pN stage as one of the most important risk factors. A strong correlation between nodal status and the occurrence of M+ was confirmed previously [ 35 , 36 , 37 , 38 , 40 ]. Even studies investigating head and neck squamous cell carcinoma, including carcinomas of the pharynx and larynx, confirmed this correlation [ 36 , 38 ].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In comparison, our study did not reveal any correlations between the localization of the tumor and the occurrence of M+, but it also identified the pN stage as one of the most important risk factors. A strong correlation between nodal status and the occurrence of M+ was confirmed previously [ 35 , 36 , 37 , 38 , 40 ]. Even studies investigating head and neck squamous cell carcinoma, including carcinomas of the pharynx and larynx, confirmed this correlation [ 36 , 38 ].…”
Section: Discussionsupporting
confidence: 83%
“…Hence, RBC transfusions ( Figure 1 ) and pN stage ( Figure 2 ) proved to be independent risk factors for M+ even when adjusted for the main confounding factors. While lymph node status was already found to be an independent prognostic factor in previous studies [ 35 , 36 , 37 , 38 ], this is the first study to report RBC transfusions as a significant risk factor for M+. The hazard ratio (HR) of developing M+ is 2.42 times higher for transfused patients compared to non-transfused patients.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…It might therefore be assumed that perineural invasion could also play a key role in the appearance of DM. Moreover, several studies report an association between vascular invasion and a higher risk of distant dissemination of disease (9,10,(15)(16)(17)(18)(19)(20). However, in the present study, vascular invasion was not found to be a relevant factor for the development of DM (P>0.005).…”
Section: Discussionmentioning
confidence: 99%